Assessment of atrial fibrillation patients' education needs from patient and clinician perspectives: A qualitative descriptive study. Issue 173 (January 2019) - Salmasi, Shahrzad; Kwan, Leanne; MacGillivray, Jenny; Bansback, Nick; De Vera, Mary A.; Barry, Arden R.; Harrison, Mark J.; Andrade, Jason; Lynd, Larry D.; Loewen, Peter
Abstract: Introduction: Patients' lack of knowledge is a key barrier to therapy adherence. We aimed to gather insights into atrial fibrillation (AF) patients' education needs from patient and clinician viewpoints. Methods: We conducted a qualitative descriptive study using purposive sampling and semi-structured interviews with AF patients and clinicians recruited from AF clinics. Data from patients and clinicians were analyzed independently and iteratively through inductive qualitative thematic analysis. Results: Eleven clinicians and 10 patients were interviewed. Three themes emerged from analysis of clinician data: (1) patients' knowledge gaps and misconceptions, (2) clinicians' experiences teaching AF patients, and (3) clinicians' suggestions for AF education programs. Four themes emerged from the patient data: (1) emotional appraisal of the disease, (2) information seeking behavior, (3) knowledge gaps, and (4) education preferences. A key finding was identification of the need for education that addresses patients' unjustified anxieties by emphasizing that AF is not fatal, and that many patients with AF live a normal life. Risk communication was identified as the most challenging aspect of AF education. In synthesizing our findings, we developed evidence-based recommendations for educational strategies for AF. Conclusion: We found that AF patients have many knowledge gaps and misconceptions, significant emotional education needs, and a positive attitude towards online and classroom education. In synthesizing our findings, we developed evidence-based recommendations which can inform the design of AF patient education programs and initiatives. Highlights: Atrial fibrillation (AF) patients have many knowledge gaps and misconceptions. AF patient education should address patients' emotional needs. AF patients' risk communication preferences are variable. AF patients frequently consult the internet to find information. AF patients have a positive attitude towards online and classroom education.